The Effect of Person Job Fit and Person Organization Fit on Innovative Work Behavior through Innovation Trust at PT. Hanjaya Mandala Sampoerna Medan - Elyzabeth Wijaya (Cita konsultindo, 2024)
The objective of this study is to assess the influence of job fit and organization fit on creative work behavior, specifically evaluated by innovation trust, at PT Hanjaya Mandala Sampoerna. The study utilizes a descriptive methodology with a quantitative approach. The investigation was carried out at PT Hanjaya Mandala Sampoerna, located in Langkat Regency. The study included a total of 184 individuals who were all workers of PT. Hanjaya Mandala Sampoerna, including both the population and the sample. The study utilizes SmartPLS software for the analysis of data. The findings indicated a clear correlation between a person's job fit (X1) and their creative work behavior (Y). The significance of the finding may be observed from the p-value of 0.000, which is less than the significance level of 0.05. Additionally, the calculated t-value of 4.954 is greater than the critical t-value of 1.972. Assessing the direct correlation between an individual's job fit (X1) and their level of trust in innovation (Z). The result indicates a statistically significant value of 0.046 <0.05, and the tcount value is 2.912 <1.972, which is higher than the t table value. The study examined the direct correlation between Person Organization Fit (X2) and Innovative Work Behavior (Y). The result indicates a highly significant value of 0.000 (less than 0.05), and a t count value of 3.673 (more than the t table value of 1.972). The findings demonstrate a clear correlation between Person Organization Fit (X2) and Innovation Trust (Z). The result indicates a statistically significant value of 0.029 (less than 0.05), with a t count value of 2.196 (more than 1.972), based on the t table. The findings demonstrate a clear correlation between faith in innovation (Z) and the manifestation of creative work behavior (Y). The result indicates a statistically significant value of 0.012 (p < 0.05) and a tcount value of 2.528 (ttable < 1.972). Innovation trust (Z) serves as an intermediary factor between person job fit (X1) and inventive work behavior (Y). The significance of the finding is evident from the p-value of 0.012, which is less than the significance level of 0.05. Additionally, the calculated t-value of 2.401 exceeds the critical t-value of 1.972. Innovation trust (Z) serves as an intermediary factor between person-organization fit (X2) and creative work behavior (Y). The result indicates a statistically significant value of 0.006 (p < 0.05) and a t count value that exceeds the critical t value from the t table (2.169 > 1.972).